Analysis of Francis Bacon’s Prose Writing Style - Sahibzada, Javed; Maroofi, Saifullah; Laftah, Susan Hussein (American International Journal of Social Science Research, 2020)
The purpose of this expositional paper was to analyze the Francis Bacon Prose Style as literary genre with reference to his essays (“Of Studies” Of Revenge” and “Of Marriage and Single Life”) Bacon’s essays have a certain unique characteristic which make us question the classification of essay. Literary review through expositional form of writing for presenting opinions based on facts from his essays was considered as a method for analyzing literary essays. The finding of this paper through analyzing his three major essays (“Of Studies” Of Revenge” and “Of Marriage and Single Life) revealed, Bacon has used various features which can be termed as: Aphoristic, Paradox, Rhetorical Device, Imagery, Analogy, and allusion for being impersonal trough saving his own personality. Bacon’s works are classified as essays for having the artistic value of Beauty and moral. Francis Bacon has distinctive features that fame his works through the ages. Bacon’s style is compact yet polished and indeed some of its conciseness is due to the skillful adaptation of Latin idiom and phrase. His sentences are pregnant and have the capability of expending into paragraph. He had a great and impressive mastery over the art of saying maximum into minimum words.